The Serial Mediating Role of Cognitive Flexibility and Digital Literacy in the Relationship Between Metacognitive Awareness and Digital Well-Being - Selman Çutuk; Zeynep Akkuş Çutuk; Rukiye Aydoğan; Jason Perez; Pablo Prieto-González (European Journal of Investigation in Health, Psychology and Education, 2026)
(1) Background: As university students increasingly engage with digital tools in their academic and daily lives, digital well-being has become an important issue. This study aimed to examine a comprehensive sequential mediation model in which cognitive flexibility and digital literacy explain the relationship between metacognitive awareness and digital well-being among university students. (2) Methods: This cross-sectional correlational study included 711 university students. Data were collected using the Metacognitive Awareness Scale, Cognitive Flexibility Inventory, Digital Literacy Scale, and Digital Well-Being Scale. The proposed model was tested using structural equation modeling, and indirect associations were examined using bootstrap analyses. (3) Results: The findings indicated that metacognitive awareness was positively associated with cognitive flexibility and digital literacy, whereas cognitive flexibility was positively associated with both digital literacy and digital well-being. Digital literacy was also positively associated with digital well-being. Bootstrap results supported significant indirect associations between metacognitive awareness and digital well-being through cognitive flexibility and digital literacy, including their sequential mediation. (4) Conclusions: These findings suggest that university students’ digital well-being can be better understood by considering metacognitive awareness, cognitive flexibility, and digital literacy together. Therefore, holistic approaches that focus on developing these three areas together may be beneficial in interventions aimed at supporting digital well-being.